Energy production for environmental issues in Turkey - Yuksel, Ibrahim; Arman, Hasan; Demirel, Ibrahim Halil (E D P SCIENCES, 2017)
Due to the diversification efforts of energy sources, use of natural gas that was newly introduced into Turkish economy, has been growing rapidly. Turkey has large reserves of coal, particularly of lignite. The proven lignite reserves are 8.0 billion tons. The estimated total possible reserves are 30 billion tons. Turkey, with its young population and growing energy demand per person, its fast growing urbanization, and its economic development, has been one of the fast growing power markets of the world for the last two decades. It is expected that the demand for electric energy in Turkey will be 580 billion kWh by the year 2020. Turkey's electric energy demand is growing about 6-8% yearly due to fast economic growing. This paper deals with energy demand and consumption for environmental issues in Turkey.
Keywords: HYDROPOWER; Energy & Fuels; Engineering